2021
DOI: 10.3390/brainsci11020200
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral Microenvironment in High-Grade Gliomas: From FLAIRectomy to Microglia–Glioma Cross-Talk

Abstract: Cellular composition and molecular signatures of the glioma core compared with infiltrative margins are different, and it is well known that the tumor edge is enriched in microglia. In this review of the literature, we summarize the role of the peritumoral area in high-grade gliomas (HGGs) from surgical and biological points of view. There is evidence on the dual role of microglia in HGGs—a scavenger-tumoricidal role when microglia are activated in an M1 phenotype and a role favoring tumor growth and infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 100 publications
0
22
0
Order By: Relevance
“…Apart from the most common glial tumors,[ 2 , 3 , 10 ] the central nervous system (CNS) can be the primary site of onset of different types of neoplasms, including neuroepithelial, neuronal, embryonal, and mesenchymal tumors. [ 1 , 27 ] Primary CNS tumors exhibit a large series of signs and symptoms, largely dependent on the specific brain location, including seizures or other neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the most common glial tumors,[ 2 , 3 , 10 ] the central nervous system (CNS) can be the primary site of onset of different types of neoplasms, including neuroepithelial, neuronal, embryonal, and mesenchymal tumors. [ 1 , 27 ] Primary CNS tumors exhibit a large series of signs and symptoms, largely dependent on the specific brain location, including seizures or other neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of microglia will not only cause damage to the central nervous system but also affect the occurrence and development of glioma ( Altieri et al, 2021 ). As the most common inducer of the inflammatory response, LPS interacts with TLRs on the cell surface to induce dimerization of TLR4 on the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that the grade of glioma is proportional to the number of infiltrating "M2"-type microglia in the microenvironment. Therefore, glioma-associated microglia and macrophages are also one of the research hotspots in the microenvironment of glioma [24]. Microglia can be activated and recruited to the lesion site within a few hours.…”
Section: Discussionmentioning
confidence: 99%